The Impact of maternal obesity and race/ethnicity on perinatal outcomes: Independent and joint effects. Issue 7 (25th May 2016) - Snowden, Jonathan M.; Mission, John F.; Marshall, Nicole E.; Quigley, Brian; Main, Elliott; Gilbert, William M.; Chung, Judith H.; Caughey, Aaron B.
Abstract : Objective: Independent and joint impacts of maternal race/ethnicity and obesity on adverse birth outcomes, including pre‐eclampsia, low birth weight, and macrosomia, were characterized. Methods: Retrospective cohort study of all 2007 California births was conducted using vital records and claims data. Maternal race/ethnicity and maternal body mass index (BMI) were the key exposures; their independent and joint impact on outcomes using regression models was analyzed. Results: Racial/ethnic minority women of normal weight generally had higher risk as compared with white women of normal weight (e.g., African‐American women, pre‐eclampsia adjusted odds ratio [aOR] 1.60, 95% confidence interval [CI]: 1.48‐1.74 vs. white women). However, elevated BMI did not usually confer additional risk (e.g., pre‐eclampsia aOR comparing African‐American women with excess weight with white women with excess weight, 1.17, 95% CI: 0.89‐1.54). Obesity was a risk factor for low birth weight only among white women (excess weight aOR, 1.24, 95% CI: 1.04‐1.49 vs. white women of normal weight) and not among racial/ethnic minority women (e.g., African‐American women, 0.95, 95% CI: 0.83‐1.08). Conclusions: These findings add nuance to our understanding of the interplay between maternal race/ethnicity, BMI, and perinatal outcomes. While the BMI/adverse outcome gradient appears weaker in racial/ethnic minority women, this reflects the overall risk increase in racial/ethnic minority women of all body sizes.